Saving the Soul of the Smart City. - Yates, Joshua J. (Hedgehog Review)
The article highlights the dangers implicit in submitting to a highly technocratic urbanism devoted primarily to optimization. It is argued that some of the things most necessary for human thriving cannot be optimized, and are greatly harmed to the extent that human try. It is stated that family, friendship, serendipity, play, dependency, trust and happiness are just a few of the things that make life meaningful and which wither in the soil of optimization.